How Does Meaning Affect the Perceived Value of Art? The Case of Chinese Calligraphy - Song, Yuqing; Radermecker, Anne-Sophie (Culture unbound, 2024)
How does meaning making affect the perceived value of art? In this paper, we focus on a unique form of art, Chinese calligraphy, to explore the effects of literal meaning on the perceived value of art combining both words and aesthetic quality. Based on a 2*4 between-subjects factorial experiment (n = 451), we find evidence that the provision of transcriptions for Chinese calligraphy artworks can have certain impact on the works’ perceived value. Specifically, our findings suggest that transcriptions enhance the appreciation of the value of the literal content and the perceived beauty of certain artwork. This paper contributes to a better understanding of the effect of meaning on the perceived value of Chinese calligraphy artworks, information supply on aesthetic experiences, and the value of Chinese calligraphy as intangible cultural heritage. Recommendations for stakeholders including auction houses are provided.